Audit Experience, Work Expense, and Professional Skepticism on Auditor's Ability in Detecting Lack - Agus Bandiyono (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Various causes of fraud in Indonesia, especially in the government sector, have decreased public trust in the government. This study aims to test empirically the effect of professional skepticism, workload, and audit experience on the ability of internal auditors to detect fraud. The object of this research is the role of auditors at the Inspectorate General of the Ministry of Finance concerning implementing their duties in detecting fraud. The selection of this object was based on the consideration that the auditors there had knowledge and experience regarding internal audits and were interested in disclosing and detecting fraud cases in the Ministry of Finance. In this study, researchers distributed 100 questionnaires from a total population of 285 auditors at the Inspectorate General of the Ministry of Finance. The analysis concluded that the audit experience has a positive but insignificant effect on the ability of internal auditors to detect fraud. The workload has a positive but not significant effect on the ability of internal auditors to detect fraud. Besides, there is a positive and very significant effect of professional skepticism on the ability of internal auditors to detect fraud.